Nanostructured Anatase Titania Spheres as Light Scattering Layer in Dye-sensitized Solar Cells. (2016) - Swathy, K.S.; Abraham, P.A.; Panicker, N. Rani; Pramanik, N.C.; Jacob, K. Stanly
Abstract: Incorporation of scattering layer on the nanocrystalline titania coating is an effective way to increase the efficiency of Dye sensitized solar cell. In this work, nanostructured titania spheres of ∼400 nm size were synthesized through modified sol gel method using ethylene glycol as coordinating ligand. The anatase titania spheres were characterized using XRD, SEM and TEM. The performance of the synthesized nanostructured spherical anatase titania were studied by coating additional layers of scattering layer over the conventional photo anode. The photovoltaic performances of the dye sensitized solar cells were measured under AM1.5G solar spectrum with light intensity of 100 mW/cm 2 . DSSC with scattering layer achieved photovoltaic parameters such as, Voc of 0.690 V, Jsc of 10.44 mA/cm 2, fill factor of 0.68 and solar to electric power conversion efficiency of 4.92%.